KERAGAAN TANAMAN KELAPA SAWIT MENGHASILKAN PADA LAHAN BEKAS TAMBANG BATUBARA - Napitupulu, Niko; Andayani, Neny; Noviana, Githa (Institut Teknologi Sawit Indonesia, 2023)
The research was on ex-coal mining land located in Kintap District, Tanah Laut Regency, South Kalimantan Province, and the oil palm plantation located in Kelumpang Selatan District, Kotabaru Regency, South Kalimantan Province. The increase in palm oil production in Indonesia is followed by increasing in the area of oil palm plantations every year. Arable land is limited, and a ban on opening new land for oil palm plantations affects oil palm companies to utilize existing marginal land for oil palm plantations. The research aims to find out and compare the growth and production of mature oil palm trees planted on ex-coal mining land and original mineral land. The study was conducted from March to April 2023 and used agronomic methods by determining sample blocks and collecting primary and secondary data. That data was obtainable by measuring trees in 2 ex-coal mining blocks and original mineral blocks. Each block consists of 30 sample trees. The data obtained were then analyzed using the t-test at a significance level of 5%. The results showed the stem circumference, number of fronds, and length of fronds on ex-coal mining land were significantly different from the original mineral land, and stem height, number of leaves, petiole width, petiole thickness, and production on ex-coal mining land didn’t show significant differences from the original mineral land.